STUDENTS’ PERCEPTIONS OF USING POWERPOINT AS LEARNING MEDIA IN ENGLISH LANGUAGE TEACHING AT JUNIOR HIGH SCHOOL - Neris Mayang Ledy; Syafryadin Syafryadin (Universitas Wiralodra, 2023)
This study is aimed at investigating students’ perceptions of using PowerPoint as a learning medium in English language teaching at a junior high school. The study was carried out at SMPN 1 Kepahiang with 30 students in the seventh grade as the subject of the study. This study combines quantitative and qualitative methodologies to examine students’ perceptions of using PowerPoint as a learning medium in English language teaching. The data was analyzed through quantitative (questionnaire) and qualitative (interview) methods. The results showed that students had positive perceptions of using PowerPoint as a teaching medium in learning English at school and were able to improve and motivate themselves. The interviews' conclusions were confirmed by the interview results, which showed that more students approved of using PowerPoint for learning. Thus, it may be said that students have positive and joyful perceptions of PowerPoint. Additionally, students believe PowerPoint to be more beneficial while learning English, particularly when it comes to boosting English activity, motivation, and competency during the learning process. Future researchers are advised to employ a larger sample, a longer time, and to utilize a PowerPoint presentation that is more appealing and varied, such as one created using Canva or another tool.